18.4L: Late‐News Paper: Full Color Flexible Top‐emission AMOLED Display on Polyethylene Naphthalate (PEN) Foil with Metal Oxide TFTs Backplane. Issue 1 (1st July 2013) - Fukui, Yusuke; Shibata, Masaomi; Tanaka, Yuji; Okumoto, Kenji; Morita, Kiyoyuki; Otake, Keiichi; Tripathi, Ashutosh Kumar; van der Putten, Bas; van der Steen, Jan‐Laurens; Tempelaars, Karin; van Leuken, Linda; Li, Flora; et al.
Abstract: We have developed a full color flexible top‐emission AMOLED display with 80 ppi resolution using In‐Ga‐Zn‐O TFT backplane on PEN foil under the maximum process temperature of 150 o C. Notwithstanding the low processing temperature, the TFTs with SiOx passivation layer show high reliability with VTH shift of less than 0.2 V at 10, 000 seconds under bias‐stress of −10 V.